Basic Auditing - Ema Mauliani; Sri Malau; Naomi Lubis (Penerbit Jurnal Indonesia, 2025)
Auditors should continue to improve their understanding of audit philosophy to be able to carry out their duties more objectively, professionally, and independently, in order to create more accurate and trustworthy audit results. The audit cycle must be carried out carefully and structured. Auditors are expected to focus more on every stage of the audit cycle, from planning to reporting, to ensure that the audit process runs effectively and efficiently. In carrying out their duties, auditors need to pay more attention to auditing norms and codes of ethics in order to maintain their professional standards and maintain public trust in the audit process carried out. Therefore, auditors need to always prioritize their integrity and independence. A more in-depth and detailed audit plan will reduce the risk of non-conformities or omissions in the implementation of the audit. Therefore, each auditor must be more thorough in preparing a mature audit plan in accordance with the complexity and objectives of the audit faced. Auditors should pay attention to the importance of audit working papers as evidence that supports every step in the audit process. The working paper must be prepared carefully, clearly, and completely so that it can be used as a strong reference in compiling audit reports. Auditors should be more transparent and firm in formulating audit opinions, by always ensuring that the opinions provided are based on strong and sufficient evidence, and can be properly accounted for. The audit report must be prepared clearly, completely, and in accordance with applicable standards. Auditors need to ensure that the audit report is understandable to stakeholders and provides enough information for informed decision-making.